In situ 4D distribution visualization of carbon-black volume fraction in cathode slurry of lithium-ion battery by multi-layered electrical resistance tomography (mlERT) - Ikeno, Natsuki; Prayitno, Yosephus Ardean Kurnianto; Sejati, Prima Asmara; Kawashima, Daisuke; Takei, Masahiro (lsevier B.V. and The Society of Powder Technology Japan., 2022)
In situ 4D (3D spatial + 1D temporal) distribution of carbon black (CB) volume fraction /CB in cathode slurry of lithium-ion battery (LIB) (CB powder and lithium cobalt dioxide (LiCoO 2) particles in NMP/PVDF solution) has been visualized by multi-layered electrical resistance tomography (mlERT). The mlERT are composed of 24 electrodes (=8 electrodes/layer 3 layers) with a newly developed multiplexer unit, which reconstructs the normalized conductivity r from the measured voltages U. The conditions of /CB is observed in the three dispersion states which are initial state, dispersing state, and fully dispersed state, under the mixing time t ¼ 0 360s and the mixing speed x ¼ 720; 400; and 200rpm. As the results, in the initial state (t ¼ 0s), the distribution of /CB is clearly visualized by the spatial r distribution from the high conductivity of /CB to the low conductivity of /Li which represents the initial position of CB powder and LiCoO 2 particles in NMP/PVDF solution. In the dispersing state (t ¼ 30 120 s), the distribution of /CB is dynamically changed as the r distribution is graduallly increased in the 3D spatial domain of mlERT which represents the dispersing CB powder within LiCoO2 particles in NMP/PVDF solution. In the fully dispersed state (t ¼ 120 360 s), the /CB is in the uniformity as the r distribution tends to be uniformly dispersed which represents the fully dispersed CB in cathode slurry. In order to evaluate the distribution visualization of /CB in the fully dispersed state by mlERT, a qualitatively-scanning electron microscope (SEM) and a quantitatively-invasive two-wire resistance measurement are tested. The qualitatively-SEM images of fully dispersed CB at the height z ¼ 5 and 20mm are observed in the distributed formation of CB powder within LiCoO2 particles in NMP/PVDF solution which agrees to the uniformity of the r distribution by mlERT. Moreover, the comparison of r distribution by mlERT to the quantitatively-invasive two-wire resistance measurement is resulted in a low root means square error RSME ¼ 0:00196% which indicates the high accuracy of the in situ 4D distribution visualization of /CB in cathode slurry of LIB by mlERT.